2022
DOI: 10.1016/j.isci.2021.103567
|View full text |Cite
|
Sign up to set email alerts
|

Self-motion illusions from distorted optic flow in multifocal glasses

Abstract: HighlightsMultifocal lenses impair vision of spectacle wearers with gazedependent distortions A model of heading perception from distorted optic flow suggest a misperception Heading perception was tested with a virtual reality-based simulation of distortions Distortions lead to gaze direction-dependent illusions in perceived vertical heading

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These solutions restrict gaze behavior to predefined lens regions, limiting visual convenience and field of view. Furthermore, progressive lenses, while effective in correcting vision, can introduce optical aberrations that compromise visual perception [5,21,1,14,25,19,24,22]. To overcome these limitations and cater to the dynamic gaze requirements of individuals with presbyopia, autofocal lenses offer a promising solution.…”
Section: Introductionmentioning
confidence: 99%
“…These solutions restrict gaze behavior to predefined lens regions, limiting visual convenience and field of view. Furthermore, progressive lenses, while effective in correcting vision, can introduce optical aberrations that compromise visual perception [5,21,1,14,25,19,24,22]. To overcome these limitations and cater to the dynamic gaze requirements of individuals with presbyopia, autofocal lenses offer a promising solution.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory research has shown that optical magnification and minification can have far reaching perceptual and physical effects. These effects include changes in apparent size of objects ( Ogle, 1950 ), changes in perceived depth ( Ames, Ogle, & Gliddon, 1932 ; Kuhl, Thompson, & Creem-Regehr, 2009 ; Ogle, 1938 ; Tong et al, 2020 ) and changes in perceived world motion ( Bruder, Wieland, Bolte, Lappe, & Steinicke, 2013 ; Sauer et al, 2022 ). Magnification and minification also alter eye movement demands and may contribute to physical symptoms like dizziness, nausea, and eyestrain often reported when people wear AR/VR devices ( Chan et al, 2022 ; Kaufeld et al, 2022 ; Saredakis et al, 2020 ; Stanney, Kennedy, & Drexler, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…How to optimize the design for distortions in general is an open question, however, because their influence on visual perception is poorly understood. Geometric distortions are associated with the swim effect, a phenomenon of unnatural or unstable perception of the environment during head or eye movements, causing instability, dizziness, tripping, and nausea [16,22,12,1]. It is unclear how those effects scale with the physical distortion of the lens and its distribution across the visual field.…”
Section: Introductionmentioning
confidence: 99%